Relative strength requirement for swallow element proper execution: a predictive test - Gorosito, M. A. (Science of Gymnastics Journal, 2013)
The present study analyzes the correlation between gymnast´s relative strength and the time in seconds that the athlete can hold the swallow on rings with the idea to identify the minimum relative strength required for the proper execution of this element. In addition, a dumbbells exercise is proposed as a convenient evaluation and training method for swallow conditioning. Furthermore, gymnast body ratios were evaluated in order to achieve whether these parameters represent an advantage or disadvantage for swallow execution on rings. A Spearman`s correlation test was used to compare the relative strength, height/sitting height and height/wingspan ratios versus the swallow holding time of 14 senior Elite level male gymnasts from the Argentinean team. A significant correlation (p<0.01) between the relative strength and the time in seconds that the swallow was held by the athletes was found, proving that the execution of this element on rings is explained almost in a 90% by the gymnast´s relative strength. No correlation between the swallow holding time and the height/sitting height and height/wingspan ratios were found. These results could provide to gymnasts and coaches with a useful tool for easily recognize if the gymnast´s physical condition is appropriate to perform a swallow on rings.